Auditory evaluation in patients with type 1 diabetes - Benito Pessin, Adriana Bueno [UNESP]; Garcia Martins, Regina Helena [UNESP]; Pimenta, Walkyiria de Paula [UNESP]; Simoes, Antonio Caetano Pereira [UNESP]; Marsiglia, Alessandra [UNESP]; Amaral, Amanda Vieira [UNESP] (Annals Publ Co, 2008)
Objectives: We performed a prospective clinical study of the cochleovestibular symptoms and the risk cofactors and characteristics of hearing loss in patients with type 1 diabetes.Methods: Group I consisted of 40 patients with type I diabetes, and group 2 consisted of 20 control subjects without diabetes. All participants answered a questionnaire, and their medical records were reviewed. They also were submitted to otorhinolaryngological examinations and to auditory tests (pure tone audiometry and acoustic immitance and auditory brain stem response [ABR] tests).Results: Dyslipidemia, hypertension, retinopathy, and diabetic neuropathy were not frequent in the patients of group 1, but incipient nephropathy was present in 47.5% of them. The most frequent cochleovestibular symptoms were tinnitus and hearing loss. Sensorineural hearing loss was found in 4 patients of group I and was predominantly bilateral, symmetric, and affecting the high frequencies, coexisting with normal vocal discrimination. These patients had a longer time from diabetes diagnosis and had poor glycemia control. A delay of ABR interpeak latency I-III was observed in 11.25% of the group I ears. All patients of group 2 presented normal audiograms and ABR tests.Conclusions: In group 1, the most frequent cochleovestibular symptoms were tinnitus and hearing loss. The sensorineural hearing loss was mild, symmetric, and predominantly high-frequency. A delay of ABR interpeak latencies was detected in the patients of group I who had normal audiometric thresholds.